Evaluating students’ perceptions of literature courses in English education: Implications for curriculum development - Ira Maisarah; Mega Fitri Wulandari; Seth Soy (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2025)
The concerns of this study were the literature used in English classrooms and students’ views on how it assists them in developing academically and professionally. Thus, its purpose was to evaluate the importance attached to literature courses in the curriculum of English Education programs. The study employed a sequential explanatory mixed-methods design. Quantitatively, a questionnaire instrument was used, which was completed by 107 students of the English Education Study Program at Universitas Bengkulu, regarding their perceptions of the implementation of literary courses, administered through Google Forms. Qualitatively, unstructured interviews provided more profound insights into the role of literature in students’ language proficiency. The results indicate that the majority of students (86%) are interested in studying literature, and they are highly engaged in their work. Those students felt that their grammar competence, vocabulary, and language skills had increased. Furthermore, 91% specifically claimed that literature enhanced their ability for critical thinking and intellectual enrichment, while 77% derived confidence in engaging with literary texts, thereby fostering further collaboration, empathy, and cultural sensitivity in their day-to-day offline routine. Thirty-five per cent of students were also encouraged to read literature. Yet, students encountered constraints such as insufficient time for studying, linguistic complexity, and exposure to unfamiliar cultural scenes. Students value literary education and the use of literature in preparing for future demands. Pedagogically, the curriculum development literature should be systematically integrated with odd in English Education, particularly instructional routines that value active learning, situated interpretation, and imaginative interaction with texts.